Analysis of the Impact of Coulomb Stress Changes of Tehoru Earthquake, Central Maluku Regency, Maluku Province - Matheus Souisa; Sisca Madonna Sapulete (Postgraduate, University of Mataram, 2021)
The Tehoru earthquake occurred due to the release of stress in rocks. There is a release of energy as an earthquake as a result of the rock elasticity limit has been exceeded because the rock is no longer able to withstand the stress. One method to determine the distribution of earthquake stress is the Coulomb stress change method. The study aimed to determine the DCS of the Tehoru earthquake, Seram Island, and the effect of the main earthquake stress release on aftershocks.Â The research results show that the DCS distribution of the Tehoru June 16, 2021 earthquake is shown with negative lobes and positive lobes. The negative lobe is found in an area that is perpendicular to the fault plane and has been identified as having experienced relaxation, so there may be still aftershocks with stress values ranging from (0.0 â€“ 0.3) bar. The dominant positive lobe occurs next to the southern end of the fault plane, too much located in the area of increasing Coulomb stress with values ranging from (0.2 - 0.6) bar